Smart grid security an end-to-end view of security in the new electrical grid - Sorebo, Gilbert N. (CRC Press, 2012)
"The Smart Grid has the potential to revolutionize electricity delivery systems, and the security of its infrastructure is a vital concern not only for cyber-security practitioners, engineers, policy makers, and utility executives, but also for the media and consumers. Smart Grid Security: An End-to-End View of Security in the New Electrical Grid explores the important techniques, challenges, and forces that will shape how we achieve a secure twenty-first century electric grid. Following an overview of the components of the Smart Grid, the book delves into the evolution of security standards and regulations and examines ways in which the Smart Grid might be regulated. The authors discuss the technical details about how metering technology is being implemented and the likely threats and vulnerabilities that utilities will face. They address the home area network (HAN) and examine distribution and transmission the foundation for the delivery of electricity, along with distributed generation, micro-grids, and operations. The book explores future concepts such as energy storage and the use of plug-in electric vehicles (PEVs) in addition to the concomitant risk for fraud and manipulation with stored energy. Consumer-related issues are discussed as they pertain to emerging ways of receiving and generating energy. The book examines dysfunctions ranging from inadvertent outages to cyber-attack and presents recommendations on how to respond to these incidents. It concludes with speculation of future cyber-security challenges and discusses new ways that the grid can be defended, such as better key management and protection. Written in a style rigorous enough for the practitioner yet accessible to a broad audience, this comprehensive volume covers a topic that is becoming more critical to industry and consumers everywhere"--